Abstract 4145771: Association Between Sleep Quality Parameters and Risk of Stroke: A Meta-Analysis of Mendelian Randomization Studies - Mahadevan, Arankesh; Prabu, Samyuktha; Patel, Mansi; Dhananjaya, Hemanth; Jog, Himanshu; Goyal, Ninia; Gawde, Rashmi; Desai, Rupak (Circulation (New York, N.Y.), 2024)
Background: Sleep quality has emerged as a potential contributor to ischemic stroke risk, and genetic associations have been increasingly investigated for this association. Our analysis aims to elucidate the current understanding of the genetic basis linking sleep quality parameters to ischemic stroke through four distinct exposure groups: short sleep duration, long sleep duration, total sleep duration, and the presence of insomnia. Method: The PubMed database was searched to find Mendelian randomization studies reporting the association between ischemic stroke and associated sleep durations and parameters using title abstract keywords and medical subject headings. The initial search yielded 76 results, of which 62 underwent title abstract screening, and nine studies were identified for full-text screening. Eight studies were included in the final analysis. The random effects model was used to pool binary outcomes as odds ratios (OR) with 95% confidence intervals (CI), and the results were presented on forest plots. P value < 0.05 was considered for statistical significance. Results: Our pooled analysis revealed a statistically significant association between insomnia and higher odds of ischemic stroke (1.11 [95% CI 1.01-1.22, p=0.03]). However, this finding was limited by high heterogeneity (I2 = 77%, p<0.01). Short sleep vs. normal sleep duration, long sleep vs. normal sleep duration, and total sleep duration did not show statistically significant associations with ischemic stroke (OR: 1.06 [1.00-1.12], 1.01 [0.94-1.08], and 0.99 [0.98-1.00], respectively). Conclusion: Our pooled analysis of Mendelian randomization studies finds a positive association between insomnia and the odds of ischemic stroke. However, the associations between sleep duration and ischemic stroke cannot be ruled out. Suggesting potential genetic underpinnings between sleep quality parameters and cerebrovascular events.